Ontologies to coordinate multiple views: Exploring document collections - Prates, Jorge Marques [UNESP]; Garcia, Rogério Eduardo [UNESP]; Eler, Danilo Medeiros [UNESP] (My University, 2014)
Multiple views of data sets can provide assistance on discovering unforeseen associations among elements contained on these sets. Thus, users are able to explore data in distinct perspectives. Ontologies are formal representations which describe data relations explicitly. Representing the underlying data into ontology, the exploratory visualization can benefit from a semantic representation to create the mappings, and might be helpful to establish relations on multiple views. In this way, we propose the application of ontology to support the mapping in the coordination process, defining how the data elements are related. Also, we present two case studies applying ontologies on exploring text collections. After these presentation, the results are compared with traditional coordination techniques.
Keywords: Coordinated; Knowledge representation; Multiple views; Ontology; Semantic mapping